2015
DOI: 10.1007/s10620-015-3830-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Opportunistic Pathogens, but Not Pre-existing Inflammation, May Be Associated with Necrotizing Enterocolitis

Abstract: At birth, fecal S100A12 concentrations were not elevated in premature infants subsequently developing NEC in this cohort. Following NEC diagnosis, S100A12 concentrations were highly elevated, suggesting that this potentially could act as a marker of disease progression. Higher detection rates of potentially pathogenic bacteria in NEC infants suggest that a range of potentially pathogenic bacteria may collectively contribute to NEC pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
12
1
Order By: Relevance
“…However, specific characteristics have been observed in the microbiota of infants developing NEC. These infants typically exhibit a reduced bacterial diversity in combination with increased levels of potentially pathogenic microorganisms (290,291). However, the trials that have been performed so far have not identified a clear pattern of dysbiosis, though they have repeatedly identified an increased abundance of Proteobacteria as well as Clostridium perfringens preceding NEC development (291)(292)(293)(294)(295).…”
Section: Infant Intestinal Microbiota and The Risk Of Neonatal Patholmentioning
confidence: 99%
“…However, specific characteristics have been observed in the microbiota of infants developing NEC. These infants typically exhibit a reduced bacterial diversity in combination with increased levels of potentially pathogenic microorganisms (290,291). However, the trials that have been performed so far have not identified a clear pattern of dysbiosis, though they have repeatedly identified an increased abundance of Proteobacteria as well as Clostridium perfringens preceding NEC development (291)(292)(293)(294)(295).…”
Section: Infant Intestinal Microbiota and The Risk Of Neonatal Patholmentioning
confidence: 99%
“…Moreover, the investigators found that fecal samples had a positive, albeit weak, Pearson's correlation between S100A12 and total bacterial CFU/g feces (r 2 = 0:40, p < 0:01) and E. coli CFU/g feces (r 2 = 0:40, p < 0:01) [55]. This suggests that S100A12 might be used as a noninvasive biomarker to help predict NEC, a significant cause of morbidity and mortality in ELBW infants [55][56][57][58]. However, a significant limitation of this study was the small number of patients enrolled (n = 68).…”
Section: S100a12 In Colitismentioning
confidence: 99%
“…However, a significant limitation of this study was the small number of patients enrolled (n = 68). A subsequent study revealed that fecal S100A12 concentrations were elevated concomitant with NEC disease progression and that multiple pathogenic bacteria were associated with this disease progression [55,56]. Additional studies by Däbritz and colleagues attempted to determine if longitudinal measurements of fecal S100A12 could detect Very Low Birth Weight (VLBW) infants at risk for intestinal distress apart from NEC.…”
Section: S100a12 In Colitismentioning
confidence: 99%
“…It has been observed that 3 months after of antibiotics persists the microbiota disruption [120]. However, antibiotic administration to neonates has been linked to several critical clinical conditions in which modiication of the microbiota composition is thought to play a relevant role, in diseases such as necrotizing enterocolitis and sepsis [121,122].…”
Section: Antibiotic Exposure and Dysbiosis In Childrenmentioning
confidence: 99%